Practice and legislation of felling residue management to prevent forest pests in European forests - Maarten de Groot; Tine Hauptman; Kristjan Ait; Flavius Bălăcenoiu; Eckehard G. Brockerhoff; Luka Capuder; Gyorgy Csoka; Mirza Dautbasic; Massimo Faccoli; Juraj Galko; Jean Claude Grégoire; Jaroslav Holuša; et al. (European Journal of Forest Research, 2026)
In the last few decades, bark beetle outbreaks have increased in European forests, triggered by extreme weather events, such as drought and windstorms. A core element of integrated pest management to control outbreaks are salvage logging and sanitation felling, i.e., the timely removal or treatment of potential brood material and already infested trees after disturbance events. Associated with these management operations as well as with regular, planned thinning and cutting, felling residues, such as treetops, branches and stumps that remain in the forest provide potentially suitable breeding material for bark beetles and may trigger further outbreak events. Although felling residue management is part of regular forest management in most of Europe, no overview exists on its use throughout the continent. To fill this gap, we gathered forest health experts from 20 European countries and used a questionnaire to provide information on felling residue management in the context of forest protection in managed forests. Relevant legislation in these countries was reviewed for regulations concerning this topic. We found that most countries have felling residue management in their legislation and/or perform it in practice. In 12 of the 20 countries, felling residue management is being applied to manage bark beetles, particularly in areas that have experienced large-scale outbreaks in the last few decades. Felling residues are mainly managed in forests dominated by Norway spruce ( Picea abies L. Karst) and pines ( Pinus spp.) (in 19 and 17 of the countries, respectively). The most frequently used management methods on a European level were piling or mulching of felling residues. These methods were used in 14 and 16 of the countries, respectively. Besides bark beetle management, use of residues for bioenergy (4 countries) and biodiversity conservation (6 countries) was reported. The diversity of felling residue management practices across Europe may reflect differences in forest policies and climatic gradients that are affecting bark beetle outbreak risks. This overview presents the variety of felling residue management applied across 20 European countries, highlighting the reasons for and implications of its use, as well as further research needs.